Synthesis and application of silver nanoparticle adsorbent produced from Amaranthus Hybridus for the removal of malachite green dye - Akeem A. bamigbade; Kayode D. Oduntan; Ruth T. Sulaiman; Ayeni Itunu; Olubunmi K. Akiode (The Proceedings of the Nigerian Academy of Science, 2025)
Nowadays the ultimate challenge on this planet called earth is to make available clean drinkable water for all. Textile industry, predominantly dye industry, represents the major contributor to water pollution in the world. The study investigated the removal of malachite green from aqueous solutions utilizing smooth pigweed (Amaranthus hybridus) assisted silver nanoparticles (AgNPs). The synthesized AgNPs were characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffractometer (XRD), UV-visible Spectrophotometry, and Scanning Electron Microscopy (SEM). TRD analysis confirmed the crystalline structure of the AgNPs. SEM image revealed that the AgNPs exhibited a spherical morphology with non-uniform granular appearance, which can be attributed to the bio-mediated synthesis process. FTIR spectrum of the AgNPs displayed peaks at 3407, 2956, 2834, 2725, 1660, 1358 and 1096 cm-1, indicating the presence of free hydroxyl groups, C-H stretching modes, C=O stretching of alkenes, carbonyl group C-OH stretching, and C-O stretching in alcohols and ethers, respectively. Adsorption studies were conducted under varying conditions, including pH, adsorbent dosage, contact time, temperature, and initial dye concentration, to determine optimal conditions and maximum adsorption capacities. The findings revealed that an increase in temperature had a minimal influence on the adsorption process. The adsorption isotherms were best described by the Langmuir, Freundlich and Tempkin models, while the Dubinin-Radushkevich model was found to be unsuitable for this adsorption process. Overall, the results suggest that AgNPs are effective adsorbents for the removal of dyes from aqueous solutions.